COVID-19 Prevention: Role of Activated Carbon - Md Sumon Reza; ABM Kamrul Hasan; Abu Saleh Ahmed; Shammya Afroze; Muhammad Saifullah Abu Bakar; Shafi Noor Islam; Abul Kalam Azad (Journal of Engineering and Technological Sciences, 2021)
Recently, Coronavirus Disease 2019 (COVID-19) has brought the whole world into a pandemic condition, where the number of infected cases and deaths is exponentially high. A number of vaccines are available for this novel virus, but these are in the preliminary stage and are also not available to everyone. As the virus is very contagious, protection and prevention are the best way to survive and get rid of this disease. The virus affects the human body by entering through the nose, mouth, and eyes, so face protection with an appropriate mask is highly advisable. Combined masks made with activated carbon (AC) can effectively adsorb the virus because of its high surface area and broad functional groups. Such combined masks can also control coronavirus transmission by capturing harmful gases and smoke as they help in decreasing the spread of the virus